2022
DOI: 10.3390/jcm11206034
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Impact of Fatigue on the Health of Polish Nursing Students during the COVID-19 Pandemic

Abstract: (1) Lockdown-related fatigue occurring during the COVID-19 pandemic is a complex problem that can be experienced in different social groups. The objective of the current study is to attempt to identify socio-demographic and lifestyle-related factors that determine the impact of fatigue on health in general as well as in physical, cognitive, and psychosocial terms and to determine whether, and to what extent, these were predictors of fatigue in nursing students during the COVID-19 pandemic. (2) The study was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…Similar associations are also found in the results of studies conducted in different parts of the world [25,50,51]. Regular physical activity has also been indicated as a factor that may play a protective role against fatigue [43]. In our pilot study, only 13.5% of respondents reported low levels of physical activity, 57% had adequate levels, and 29.5% had high levels.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Similar associations are also found in the results of studies conducted in different parts of the world [25,50,51]. Regular physical activity has also been indicated as a factor that may play a protective role against fatigue [43]. In our pilot study, only 13.5% of respondents reported low levels of physical activity, 57% had adequate levels, and 29.5% had high levels.…”
Section: Discussionsupporting
confidence: 88%
“…In the authors' own study, the overall severity of fatigue according to the Modi ed Fatigue Impact Scale (MFIS) was 17, suggesting a low level. In studies conducted directly during the pandemic COVID-19 or in patients diagnosed with chronic COVID-19, the level of estimated fatigue was at a much higher level [43,45,46]. It is di cult to comment on these results because no studies were found in the literature that were consistent with the authors' study.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations